Subsequent commutation failure suppression strategy of hybrid cascaded HVDC system based on coordinated control of CEC and VDCOL - He Wang; Daqian Zhang; Jing Bian; Jiazhi Guo; Shiqiang Li (IET Energy Systems Integration)
Abstract The inverter side of hybrid cascaded HVDC adopts the structure of Modular Multilevel Converter (MMC) in series with Line Commutated Converter (LCC). The complete system amalgamates the advantages of LCC with MMC, but it also makes the interaction process of multi‐controller more complicated during the failure of the system. Therefore, through the analysis of the controller interaction process during the system fault, this paper proposes a multi‐controller coordinated control strategy based on the inverter side of the hybrid cascaded HVDC system, which can suppress the subsequent commutation failure of the system and take into account the recovery characteristics of the system during the fault, which has certain practical application value. Initially, the operational properties of current error control (CEC) and voltage‐dependent current limit control (VDCOL) are examined, and a coordinated control technique for subsequent commutation failure suppression and rapid power recovery during fault is proposed. Secondly, aiming at the problem of power return between MMC after VDCOL regulation, the new VDCOL control curve is coordinated to improve the MMC control strategy to ensure stable recovery during system failure. Finally, the simulation model is built in PSCAD/EMTDC simulation environment. The simulation results indicate that the proposed control technique can successfully achieve the synchronisation of commutation failure suppression and rapid, stable power restoration, thereby enhancing the operational performance of hybrid cascaded HVDC.